Penerapan Model Pembelajaran Kooperatif Investigasi Kelompok Sebagai Upaya untuk Meningkatkan Hasil Belajar Fisika Pada Materi Gaya Pada Siswa Kelas VIII SMP Negeri 17 Halmahera Selatan - Ernawati Muhtar (Peneliti.net, 2022)
This research is a PTK research with a pre-test post-test design with several groups. The purpose of this study was to determine the increase in student learning outcomes in solving style and acceleration questions with the group investigative learning model. The population in this study were all students of class VIIISMP Negeri 17 Halmahera Selatan. There were 87 students and 25 students as a sample were part of the population. Data collection used the pre-test and post-test techniques to find out the increase in learning outcomes in solving style and acceleration questions with the group investigative cooperative learning model. From the research results obtained an increase in student learning outcomes, namely 0.64 which is implemented moderately. Where in the initial test and post test increased classically and individually from an average of 44.41 to 80.46. So it can be said that learning with the cooperative model of group investigation on style and acceleration can improve student learning outcomes